2004
DOI: 10.1086/383137
|View full text |Cite|
|
Sign up to set email alerts
|

First Star Signature in Infrared Background Anisotropies

Abstract: (Abridged) Recent cosmic microwave background anisotropy results from the Wilkinson Microwave Anisotropy Probe suggest that the universe was reionized at a redshift around 20. Such an early reionization could arise through the ionizing radiation emitted by metal-free population III stars at redshifts of 10 and higher. We discuss infrared background (IRB) surface brightness spatial fluctuations from such a generation of early star formation. We show that the spatial clustering of these stars at tens of arcminut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
100
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 57 publications
(97 reference statements)
5
100
0
Order By: Relevance
“…• 5 and its spectral energy distribution (SED) should be cutoff due to the Lyman break at wavelengths 1[(1 + z)/10] μm (Cooray et al 2004;Kashlinsky et al 2004). Present measurements of the mean CIB levels are based on the DIRBE and IRTS data and suggest a substantial excess over the contribution from known galaxy populations (Dwek & Arendt 1998;Gorjian et al 2001;Arendt & Dwek 2003;Matsumoto et al 2005).…”
Section: No 1 2010 Cib Fluctuations In Deep Spitzer Irac Images 11mentioning
confidence: 98%
See 1 more Smart Citation
“…• 5 and its spectral energy distribution (SED) should be cutoff due to the Lyman break at wavelengths 1[(1 + z)/10] μm (Cooray et al 2004;Kashlinsky et al 2004). Present measurements of the mean CIB levels are based on the DIRBE and IRTS data and suggest a substantial excess over the contribution from known galaxy populations (Dwek & Arendt 1998;Gorjian et al 2001;Arendt & Dwek 2003;Matsumoto et al 2005).…”
Section: No 1 2010 Cib Fluctuations In Deep Spitzer Irac Images 11mentioning
confidence: 98%
“…It is now thought that the first stars were very massive (see review by Bromm & Larson 2004), in which case theoretical models indicate they may produce a detectable contribution to the mean level of the near-IR CIB (Santos et al 2002;Salvaterra & Ferrara 2003;Kashlinsky 2005b;Fernandez & Komatsu 2005). They are also expected to have left a measurable imprint in CIB anisotropies (Cooray et al 2004;Kashlinsky et al 2004). The intuitive reasons why these fluctuations would be significant are (1) if massive, such stars would emit at light to mass ratios ∼10 4 -10 5 higher than the present-day stellar populations leading to significant CIB flux levels; (2) assuming that the Pop III era occupied a comparatively narrow epoch in time (say Δt ∼ a few hundred million years) there should be a higher amplitude of relative CIB fluctuations (∝ 1/ √ Δt); and (3) it is expected that within the framework of the concordance ΛCDM model the first stars formed out of rare high peaks of the underlying density field and, hence, their correlation properties would be amplified.…”
Section: Introductionmentioning
confidence: 99%
“…If so, this component would dominate small scales leading to significant modification of the history of collapse (and possibly formation of the first sources), resulting in greater rates of cosmic infrared background (CIB) production at z > 10. CIB contains emissions produced over the entire history of the universe including from sources inaccessible to direct telescopic studies (see the review by Kashlinsky 2005) with early stars and BHs contributing to its near-IR (∼1-5 μm) fluctuation component (Cooray et al 2004;Kashlinsky et al 2004). In this context, Kashlinsky (2005) and Kashlinsky et al (2007b) have identified from deep Spitzer data significant CIB fluctuations remaining on sub-degree scales after subtracting individual galaxies to faint levels.…”
Section: Introductionmentioning
confidence: 99%
“…Searches for this radiation based on absolute photometry have proven problematic due to confusion with the Zodiacal foreground. Instead of the absolute background, in Cooray et al (2004), we proposed to develop a near-infrared sounding rocket experiment, CIBER, to conduct a deep search for extragalactic background fluctuations from the epoch of reionization associated with first-light galaxies.…”
Section: Introductionmentioning
confidence: 99%